Gogol as an Historian and the Development of Russian Oriental Studies - Vater, Roman (Jama'a: an Interdisciplinary Journal of Middle East Studies, 2005)
Exemplary of the alliance between literature, social thought and Oriental studies is the Russian writer Nikolai Gogol's essay 'Al-Ma'mun: an Historical Overview'. The essay, a social and political parable, reveals Gogol to be an original historiographer, an erudite scholar of the early Islamic period as well as an ardent opponent of czarist despotism. In tracing the development of academic Oriental studies in Russia from the early 18th century until the October Revolution in 1917, the article draws attention to the Orientalist biases of Gogol and his contemporaries. It proposes a concept of 'popular Orientalism' and allocates Gogol's 'Al-Ma'mun' to that genre in Russian letters.